Renal pelvic urothelial carcinoma with imaging features presenting as renal infarction 1 case report and literature review - Haidong Yang; Wenli Yang; Nanjun Duan; Jing Luo; Zhengyan Yang; Weiran Zhang; Wei Feng; Haifeng Wang (Urology Case Reports)
Renal pelvic cancer is relatively rare in clinical practice, and renal pelvic cancer characterized by renal infarction is even rarer. We here report a case of renal pelvic urothelial carcinoma with squamous metaplasia with renal infarction as the main imaging feature, and summarize the imaging manifestations of some rare renal pelvic carcinomas. Conclusion: The imaging features of renal pelvis cancer are diverse and often confused with some benign and malignant diseases, suggesting that extra caution should be exercised in the diagnosis and treatment of renal pelvis cancer.